1997
DOI: 10.1093/jmedent/34.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on Chrysomya rufifacies (Diptera: Calliphoridae) Development

Abstract: Growth curves were studied for the egg, larva, and pupa of Chrysomya rufifacies (Macquart) under mean cyclic temperatures of 15.6, 21.1, 26.7, and 35.0 degrees C and a constant temperature of 25.0 degrees C. Development from egg to adult under all regimes ranged from 190 to 598 h. A constant temperature of 25 degrees C produced a range of pupation times from 134 to 162 h, with adult emergence ranging from 237 to 289 h. The maximal preferential temperature of 35.1 degrees C was determined for maggots using a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 0 publications
2
82
1
1
Order By: Relevance
“…Greenberg (1990) and Goff (2001) reported that members of Calliphoriinae and Luciliinae were night active species and could lay their eggs during night, but in low numbers. However, no egg was observed in our early morning investigations on the material left in the study site in night, in accordance with results of Byrd & Butler (1997) and Haskell et al (1997). Daytime investigations in mornings and afternoons revealed that the hours from midday to evening were the times when eggs were laid in dense amounts.…”
Section: Resultssupporting
confidence: 93%
“…Greenberg (1990) and Goff (2001) reported that members of Calliphoriinae and Luciliinae were night active species and could lay their eggs during night, but in low numbers. However, no egg was observed in our early morning investigations on the material left in the study site in night, in accordance with results of Byrd & Butler (1997) and Haskell et al (1997). Daytime investigations in mornings and afternoons revealed that the hours from midday to evening were the times when eggs were laid in dense amounts.…”
Section: Resultssupporting
confidence: 93%
“…The concept of plasticity, an environmental response, in blow fly developmental phenotypes is widely appreciated, and such studies will likely continue. The effect of temperature on development rates has resulted in numerous studies of species-specific developmental times under laboratory-controlled treatments (17,18,91). Such studies aid investigators in predicting development rates under field conditions experienced in real-world casework (57).…”
Section: Figurementioning
confidence: 99%
“…The developmental rate of fly larvae depends primarily upon the environmental temperature-the higher the temperature, the faster the development and the lower the temperature, the slower the development. Earlier work has been conducted on the developmental rate of forensically important insects, e.g., blowfly, Chrysomya albiceps (Wiedemann) (Queiroz 1996;Marchenko 2001), C. rufifacies (Byrd and Butler 1997;Jenson and Miller 2001), C. megacephala (Wells and Kurahashi 1994;Jenson and Miller 2001), Calliphora vicina (Robineau-Desvoidy) (= C. erythrocephala Meigen) (Davies and Ratcliffe 1994;Anderson 2000;Marchenko 2001;Ames and Turner 2003), Calliphora vomitoria L. (Greenberg and Tantawi 1993;Davies and Ratcliffe 1994;Marchenko 2001;Ames and Turner 2003), Calliphora dubia (Macquart) (Dadour et al 2001), Protophormia terraenovae (Robineau-Desvoidy; Greenberg and Tantawi 1993;Marchenko 2001;Grassberger and Reiter 2002), Phormia regina (Meige) (Anderson 2000;Byrd and Allen 2001;Marchenko 2001), Eucalliphora latifrons (Hough), Lucilia illustris (Meigen) (Anderson 2000), Phaenicia (= Lucilia) sericata (Meigen) (Anderson 2000;Grassberger and Reiter 2001;Marchenko 2001); muscid fly, Muscina stabulans (Fallén) (Marchenko 2001;Mascarini and Prado 2002), Muscina assimilis (Fallén) (Marchenko 2001), Ophyra aenescens (Wiedemann), Ophyra capensis (Wiedemann) (Lefebvre and Pasquerault 2004); flesh fly, Sarcophaga tibialis Macquart (Musvasva et al 2001), Boettcherisca septentrionalis Rohdendorf (Marchenko 2001); and the beetle, Dermestes maculatus DeGeer …”
Section: Introductionmentioning
confidence: 99%